Polyneuropathy improvement following autologous stem cell transplantation for POEMS syndrome - Karam, Chafic (Neurology, 2015)
OBJECTIVE: To study the evolution of the neuropathy and long-term disability in a large cohort of patients with POEMS (polyneuropathy, organomegaly, endocrinopathy, M protein, and skin changes) syndrome following autologous stem cell transplantation (ASCT). METHODS: Retrospective chart review documenting the clinical, electrophysiologic, and laboratory characteristics of patients with POEMS syndrome undergoing ASCT at Mayo Clinic, Rochester. RESULTS: Sixty patients with a median follow-up time of 61 months were studied. All patients had peripheral polyneuropathy and demonstrated neurologic improvement after ASCT (apart from one patient who died early). Before ASCT, 27 patients (45%) required a wheelchair and 17 (29%) required a walker or foot brace. At the end of the follow-up period, no patient was using a wheelchair and 23 patients (38%) were using a foot brace. The median Neuropathy Impairment Score improved from 66 to 48 points at 12 months and to 30 points at most recent follow-up (p < 0.0001). Median Rankin Scale score improved from 3 to 1.5 (p < 0.0001). Vascular endothelial growth factor levels decreased from a median of 452 to 63.5 pg/mL (p < 0.0001). The ulnar compound motor action potential amplitude (median) improved from 4.3 to 7.6 mV (p < 0.0001) and ulnar compound motor action potential conduction velocity (median) improved from 34 to 51 m/s (p < 0.0001). Predicted forced vital capacity improved from 81% to 88% (p < 0.0001). Periengraftment syndrome occurred in 24 patients. Fourteen patients required additional chemotherapy and/or radiation following ASCT, but there was no clinical deterioration in the neuropathy in any of these patients. Six patients died: 1 due to POEMS, 1 due to failed engraftment, and 4 due to other malignancies (2 myelodysplastic syndrome, 1 lymphoma, 1 metastatic lung cancer). CONCLUSION: Patients with POEMS syndrome who undergo ASCT have a significant and meaningful improvement of their neuropathy by multiple measurements during both short and long-term follow-up, which corresponds to reduction in morbidity and disability (none are in wheelchair long-term). Periengraftment syndrome was common but manageable. Fatal complications, although rare, did occur, usually in association with other malignancies. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with POEMS syndrome, ASCT improves neuropathy-related function.